BERBAGAI CARA PENGEMBANGAN ILMU DALAM DUNIA PENDIDIKAN - Anggit Grahito W, Oka Irmade (UNIVERSITAS SLAMET RIYADI, 2015)
This article deals with science development method. The substantion is methods to acquireknowledge from some perspective, development scientific and unscientific knowledge method,concepts and type research throught quantitative and qualitative method, the distinction ofknowledge development from other knowledge. From those four substantion then it explained oneby one in detail. The scientific method must follow these steps: formulating problem/question,doing observation, formulating a hypothesis, doing experiment, collecting and analyzing resultsand making conclusion. So that we can understood those knowledge development method itself.Keyword : science development method